Bermain bagi anak, bukan sekedar bermain - Muhammad Idrus (Islamic University of Indonesia, 2002)
Playing for childreen is not only playing something like adult seen. But also exploring his or her surround, knowing each others. Playing for children could he a good time for parent to transform a good value. Refer to what Rasulullah said,